2014
DOI: 10.1890/es13-00170.1
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance alters the response of consumer communities towards warming: a mesocosm study with biofilm‐dwelling ciliates

Abstract: Citation: Marcus, H., J. K. Wey, H. Norf, and M. Weitere. 2013. Disturbance alters the response of consumer communities towards warming: A mesocosm study with biofilm-dwelling ciliates. Ecosphere 5(1):10. http://dx.Abstract. Environmental warming can have negative effects on the carrying capacity of communities because metabolic rates increase at the expense of biomass. Here, we tested the hypothesis that such warming effects are reversed in communities experiencing disturbance, as temperature-driven growth pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Disturbance and distributions -page 6 also increase and modify competitive interactions consistent with H1 Totland 2005, Olsen and. Looking to other systems I note one experimental study of biofilm-dwelling ciliates that found that disturbance reduced some effects of artificial warming on community change, again consistent with H1 (Marcus et al 2014). Microcosm studies with single species and species combinations have highlighted that competitive hierarchies determine speciestemperature distributions for fruit flies indicating that similar dynamics operate in these taxa under these conditions ).…”
Section: Appendix 1 Disturbance and Distributions -Pagementioning
confidence: 69%
“…Disturbance and distributions -page 6 also increase and modify competitive interactions consistent with H1 Totland 2005, Olsen and. Looking to other systems I note one experimental study of biofilm-dwelling ciliates that found that disturbance reduced some effects of artificial warming on community change, again consistent with H1 (Marcus et al 2014). Microcosm studies with single species and species combinations have highlighted that competitive hierarchies determine speciestemperature distributions for fruit flies indicating that similar dynamics operate in these taxa under these conditions ).…”
Section: Appendix 1 Disturbance and Distributions -Pagementioning
confidence: 69%
“…Sandy substrates may retain more nutrients than rock surfaces do because of more interstitial space (Hossain et al 2014), and the two substrate types may be exposed to different regimes of mechanical disturbance due to water flow. Both resource availability and disturbance can change the direction and magnitude of temperature effects on assemblages (Norf & Weitere 2010;Marcus et al 2014). Moreover, sand can be a different substrate depending on its grain size or composition, and retain fine organic material differently.…”
Section: Discussionmentioning
confidence: 99%
“…These factors affect the structure of the ciliate assemblages (e.g. Foissner & Berger, 1996) and could influence how ciliate assemblages respond to temperature differences (Norf & Weitere, 2010;Marcus et al, 2014). We expected ciliate assemblages on submerged rock surfaces to be more resource limited than on sandy substratum and thus predict a stronger reduction in biomass and alpha diversity with increasing temperature on rock compared with sandy substratum.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations